Progressive iron overload in middle-aged mice impairs olfactory function, triggers lipid oxidation and induces apoptosis - Deng, Lin; Luo, Qihui; Liu, Yucong; Wang, Yao; Xiong, Zongliang; Wang, Hongping; Zhao, Lu; Jia, Lanlan; Shi, Riyi; Huang, Chao; Chen, Zhengli (Frontiers in Pharmacology, 2024)
IntroductionThis study aims to investigate the progressive impact of chronic iron overload on the olfactory bulb, a region significantly affected in early neurodegenerative diseases like Parkinson’s and Alzheimer’s. The focus is on understanding how iron accumulation leads to oxidative stress, mitochondrial dysfunction, and neuronal damage over time in middle-aged mice.MethodThe mice were continuously administered FC for a duration of 16 weeks, and the olfactory behavior of the mice was observed at intervals of 4 weeks. Inductively coupled plasma mass spectrometry (ICP-MS) was employed to detect alterations in iron content within the olfactory bulb of the mice, while levels of lipid peroxidation and antioxidant indexes were assessed using biochemical kits. Additionally, western blotting and qPCR techniques were utilized to analyze transcriptional and expression changes in proteins and genes related to iron metabolism. Furthermore, microstructural modifications as well as mitochondrial observations were conducted through paraffin sectioning and transmission electron microscopy (TEM).ResultA significant and progressive increase in iron accumulation in the olfactory bulb, starting from week 8 and peaking at week 16. This accumulation coincided with a decline in olfactory function observed at week 12. Key markers of oxidative stress, such as 4-HNE and MDA, were elevated in specific layers, and antioxidant defenses were reduced. Mitochondrial damage became evident from week 8, with caspase-3 activation indicating increased apoptosis, particularly in the granular layer. This study is to demonstrate the link between chronic iron overload and progressive olfactory dysfunction in the context of neurodegenerative diseases. It provides evidence that iron-induced oxidative stress and mitochondrial damage in the olfactory bulb contribute to early sensory deficits, suggesting that the olfactory bulb’s selective vulnerability can serve as an early biomarker for neurodegenerative conditions.ConclusionChronic iron overload leads to progressive oxidative damage, mitochondrial dysfunction, and apoptosis in the olfactory bulb, causing sensory deficits. Targeting iron accumulation and oxidative damage may offer new strategies for early intervention in neurodegenerative diseases, highlighting the importance of addressing iron dysregulation.